Papers of David Wills Cooke - Wills Cooke, David, 1937-2018. (1811)
The collection comprises a variety of papers relating to David Wills Cooke and his family and includes photographs of his father Sidney Bertram Wills Cooke as a child and young man, photocopies, an autobiography of Arthur Wills and Sidney Bertram Wills Cooke, newspaper clippings of the Marngrook debate and a handwritten family tree compiled by David Wills Cooke.
Manuscript reference number: MS 10452.
Associated materials: Papers of Terry Wills Cooke, 1794-2016 MS 10257.
Brother of Terry Wills Cooke and father of Kaz Cooke.
Keywords: Wills Cooke, David, -- 1937-2018 -- Archives; Cooke, Sidney Bertram Wills -- 1907-1993.; Wills, Arthur